Answer:
The sum is equal to 5
Step-by-step explanation:
we know that
The algebraic expression of the phrase " the sum of negative two squared plus one" is equal to
![(-2)^{2}+1\\=4+1\\=5](https://tex.z-dn.net/?f=%28-2%29%5E%7B2%7D%2B1%5C%5C%3D4%2B1%5C%5C%3D5)
P (A and B) = P(A) * P(B)...answer is D
Answer:
dylan has more water
Step-by-step explanation:
1000 milliliters = 1 liter
therefore 600 milliliters = .6 liters
1 - .6 = .4
the liter has .4 more liters of water or 400 more milliliters
Answer:
12m8(2m2)3
4
m5
=24m19
Step-by-step explanation:
6.
4x^2 + 4 = 0
Divide both sides by 4
x^2 + 1 = 0
Use the quadratic formula since this cannot be factored.
x = (-b +- sqrt(b^2 - 4ac))/(2a)
x = +- sqrt(-4(1)(1))/2
x = +- sqrt(-4)/2
x = +- 2i/2
x = +- i
x = i or x = -i
Quicker solution:
If you have x^2 = number, then
x = +- sqrt(number)
Once you get to
x^2 + 1 = 0
Subtract 1 from both sides
x^2 = -1
Apply the quick method
x = +- sqrt(-1)
x = +- i
8.
2x^2 + 50 = 0
Divide both sides by 2
x^2 + 25 = 0
Subtract 25 from both sides
x^2 = -25
Apply quick method
x = +- sqrt(25)
x = +- 5i
x = 5i or x = -5i